High resolution magnetic resonance imaging of the anterior visual pathway in patients with optic neuropathies using fast spin echo and phased array local coils. Issue 5 (May 1995) - Gass, A; Barker, G J; MacManus, D; Sanders, M; Riordan-Eva, P; Tofts, P S; Thorpe, J; McDonald, W I; Moseley, I F; Miller, D H
Abstract : High resolution MRI of the anterior visual pathways was evaluated using frequency selective fat suppressed fast spin echo (FSE) sequences in conjunction with phased array local coils in patients with optic neuropathies. Fifteen normal controls and 57 patients were examined. Coronal T2 weighted fat suppressed FSE images were obtained in 11 minutes with an in plane resolution of 0.39 x 0.39 mm. The optic nerve and its sheath containing CSF were clearly differentiated. Central retinal vessels were often visible. In demyelinating optic neuritis and in anterior ischaemic optic neuropathy high signal within the nerve was readily delineated. Meningiomas and gliomas involving the optic nerve were precisely visualised both in the orbit and intracranially. Extrinsic compression of the optic nerves was readily visualised in carotid artery ectasia and dysthyroid eye disease. Enlarged subarachnoid spaces around the optic nerves were demonstrated in benign intracranial hypertension. High resolution MRI of the anterior visual pathway represents an advance in the diagnosis and management of patients presenting with optic neuropathy.